Pelatihan Berbasis Teknologi terhadap Intensi Berwirausaha - Hari Mulyadi; Sulastri Sulastri; Nadila Dewi Kusnindar (Universitas Pendidikan Indonesia, 2021)
This research aims to find out the description technology based training and entrepreneurial intention. The design of this study is cross sectional using an explanatory approach to surveys. The unit of analysis was 104 students of the class XII IOP (Instrumentation and Process Automation) at SMK Negeri 1 Cimahi. This research uses quantitative methods. With the data analysis technique used is a path analysis with SPSS computer software version 25.0. The results of the study can be known that 1) the description technolog-based training is in a effective category 2) the description of entrepreneurial intention is in a very high category, 3) the description of technology-based training has an influence of 45,2% on entrepreneurial intention. From the results of hypothetical testing research, it can be known that technology-based training have a significant effect on entrepreneurial intention.